Interphase cytogenetics for the detection of the t(11;22)(q24;q12) in small round cell tumors. - Giovannini, M (1992)
Among the small round cell tumors differential diagnosis is particularly difficult for their undifferentiated or primitive character. In this mixed group of tumors, only the primitive neuroectodermal tumors, which include Ewing's sarcoma (ES), show the unique and consistent feature of the (11;22)(q24;q12) translocation, which can therefore be considered a hallmark of these neoplasias. We analyzed four primitive neuroectodermal tumor cell lines, one osteosarcoma cell line, and 11 patients by fluorescent in situ hybridization with cosmid clones 23.2 and 5.8, bracketing the t(11;22) at 11q24. Metaphase spreads from tumor cell lines, and from biopsy specimens of three patients with ES were analyzed. In the remaining eight patients comprising five ES, two small cell osteosarcomas and one chronic osteomyelitis, only nuclei preparations were available for analysis. We detected the t(11;22) in interphase nuclei of the four primitive neuroectodermal tumor cell lines, of three patients in which the karyotype demonstrated the translocation and in five cases of ES in which cytogenetic analysis had not been possible. Two cases of small cell osteosarcoma and one chronic osteomyelitis were also analyzed and were both normal with respect to the t(11;22). By analyzing cell lines and small round cell tumor samples by fluorescent in situ hybridization, we established that interphase cytogenetics is a rapid alternative to chromosomal analysis for the detection of the t(11;22) and represents an invaluable tool for the differential diagnosis of small round cell tumors.